Baricitinib reverses HIV-associated neurocognitive disorders in a SCID mouse model and reservoir seeding in vitro - Gavegnano, Christina (J Neuroinflammation, 2019)
BACKGROUND: Since HIV-associated neurocognitive disorders (HANDs) occur in up to half of HIV-positive individuals, even with combined antiretroviral therapy (cART), adjunctive therapies are needed. Chronic CNS inflammation contributes to HAND and HIV encephalitis (HIVE). Baricitinib is a JAK 1/2 inhibitor approved in the USA, EU, and Japan for rheumatoid arthritis, demonstrating potent inhibition of IL-6, D-dimer, CRP, TNF-α, IFN-α/β, and other pro-inflammatory cytokines. METHODS: Our modified murine HAND model was used to evaluate the ability of baricitinib to cross the blood-brain barrier (BBB) and modulate monocyte/macrophage-driven HAND. Severity of HAND was measured by assessing cognitive performance of low- and high-dose baricitinib treated versus untreated HAND mice. The severity of brain neuroinflammation was evaluated in these mouse groups after flow cytometric analyses. We also assessed the ability of baricitinib to block events in myeloid and lymphoid cells in vitro that may undergird the persistence of HIV in the central nervous system (CNS) in primary human macrophages (Mϕ) and lymphocytes including HIV replication, HIV-induced activation, reservoir expansion, and reservoir maintenance. RESULTS: In vivo, both doses of 10 and 50 mg/kg qd baricitinib crossed the BBB and reversed behavioral abnormalities conferred by HIV infection. Moreover, baricitinib significantly reduced HIV-induced neuroinflammation marked by glial activation: activated microglia (MHCII(+)/CD45(+)) and astrogliosis (GFAP). Baricitinib also significantly reduced the percentage of p24+ human macrophages in mouse brains (p < 0.05 versus HAND mice; t test). In vitro, baricitinib significantly reduced markers of persistence, reservoir size, and reseeding in Mϕ. CONCLUSION: These results show that blocking the JAK/STAT pathway reverses cognitive deficits and curtails inflammatory markers in HAND in mice. Our group recently reported safety and tolerability of ruxolitinib in HIV-infected individuals (Marconi et al., Safety, tolerability and immunologic activity of ruxolitinib added to suppressive ART, 2019), underscoring potential safety and utility of JAK inhibitors for additional human trials. The data reported herein coupled with our recent human trial with JAK inhibitors provide compelling preclinical data and impetus for considering a trial of baricitinib in HAND individuals treated with cART to reverse cognitive deficits and key events driving viral persistence. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12974-019-1565-6) contains supplementary material, which is available to authorized users.